Validating cultural landscape in consumer brand preferences / Ida Izumi Abdollah - Abdollah, Ida Izumi (2019)
Culture has played a significant role in all aspects of human life affecting individual behaviours and decisions making. To ascertain, understand and interpret its impact, cultural frameworks are adopted. Since the past Malaysian cultural studies has relied on Western based frameworks to explain the Malaysian cultural related behaviors Such frameworks are based on the assumption of population homogeneity However, due to some unique and critical shonfall of these frameworks, it may not be a complete yardstick to assess consumer behaviour in an ethnically diverse population. In addition to this, another major shortfall in many Malaysian cultural based studies is the ethnicity scope, which has always been too narrow; limiting to Malays, Chinese and Indian ethnics only, while ignoring the other ethnics. As such1 the outcomes of the studies may not adequately reflect not explain the Malaysian consumer cultural behaviours. In an effort to fill the gap, this study is tailored in a local setu'ng to explores potential cultural factors that are more reflective of the Malaysian population. Qualitative and quantitative procedures are employed with more than 1000 consumers from different ethnics participated in the study. The procedures include literature reviews, focus group interviews, expert opinions, pilot test, multivariate test of normality, Exploratory Factor Analysis (EFA), Confirma’mry Factor Analysis (CFA), Pearson Correlation Analysis, Reliability Test, Validity Test and Multiple Regression Analysis. From the procedures seven farms were identified; Selfness, Religjosity, Humanity, Communion, Ethnic Identity, Moralistic and Environmentalism. The factors have been empirically tested for unidimensionality, reliability and validity, indexed a clearly good Infidel fit. The nature of the seven factors accommodates the diversity perspective of the Malaysian consumer cultural behaviors. Humanity, moralistic, religiosity and ethnic identity factors are relatively newer factor, indicates a diversion fi'om the existing cultural frameworks. This has provided an alternative cultural platform that would be more reflective of the Malaysian populations. In the elder of ranking, Ethnic identity ranked the most important followed by Environmentalism, Selfness and Religiosity factors respectively, as being determinant of brand preference. This supports the View where individuals see themselves as part of a social group, formed by laterally extended relationships rather than pursuing their own personal interests at the expense of others. Therefore, thongh consumers are more likely to prefer brands of which attributes match their own selfimage, self-expression and lifestyle, yet at the same time emphasized the needs and tolerance towards the community and social responsibilities. In the context of marketing, the findings suggest that Malaysian consumers tend to prefer brands with compatible abstract meanings as a function of Religiosity, Selfness, Humanity, Communion, Ethnic identity, Moralistic and Environmentalism, where such associan'ons are seen from simultaneous perspectives of preservation of individual life, society and nature. The knowledge of the determinant factors provides useful insight for marketer towards focusing and directing marketing efforts towards determinant factors for optimum outcomes. This knowledge is critical when introducing an existing brand into a culturally distinct market as well as to ensure that the correct positioning of their brands in the maxket.